2009
DOI: 10.2324/gomu.82.167
|View full text |Cite
|
Sign up to set email alerts
|

High Impact Polymer Alloy

Abstract: We have already represented that high impact mechanism of polyketone/polyamide alloy (PK/PA) is enhanced by the moisture absorption. It was thought the high impact mechanism depends on ductility caused by the moisture absorption of the alloy. This time we have investigated the nano-meter level phase separation structure of PK/PA alloys by using a TEM, an EELS and a 3D-TEM observation. It is found that the PK rich phase and the PA rich one form their co-continuous structure. Surprisingly, the three-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…However, a lamellar-like structure was detected even in the K90A10 alloy in the 3D-TEM image, albeit not clearly (Figure S2(c) the Supporting Information). 4,5 This indicates that PA plays an important role in forming the lamellar-like structure. The results of a previous 3D-TEM study suggested that there are characteristic spherical domains on a scale of 50-200 nm in the PK-rich alloys, K90A10 or K80A20 (Figure S2 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…However, a lamellar-like structure was detected even in the K90A10 alloy in the 3D-TEM image, albeit not clearly (Figure S2(c) the Supporting Information). 4,5 This indicates that PA plays an important role in forming the lamellar-like structure. The results of a previous 3D-TEM study suggested that there are characteristic spherical domains on a scale of 50-200 nm in the PK-rich alloys, K90A10 or K80A20 (Figure S2 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 93%
“…The results of a previous 3D-TEM study suggested that there are characteristic spherical domains on a scale of 50-200 nm in the PK-rich alloys, K90A10 or K80A20 (Figure S2 in the Supporting Information). 4,5 Figure 4b shows that there are cocontinuous spherical domains in the K60A40 alloy. These cocontinuous spherical domains of ca.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations